Resin compositions, cured products, adhesive sheets, laminates, and printed circuit boards
Patent Information
- Application Number
- JP2025046699
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2026-10-06
AI Technical Summary
【0010】 本開示によれば、銅に対して優れた接着性を有し、且つ、低誘電特性を有する樹脂組成物を提供することができる。また、本開示によれば、上記樹脂組成物の硬化物、並びに、上記樹脂組成物を用いた接着シート、積層体及びプリント配線板を提供することができる。
Smart Images

Figure 2026156820000001 
Figure 2026156820000002 
Figure 2026156820000003
Abstract
Description
[Technical Field]
[0001] This disclosure relates to resin compositions, cured products, adhesive sheets, laminates, and printed circuit boards. [Background technology]
[0002] Printed circuit boards and multilayer circuit boards using them are used in products such as mobile communication devices like mobile phones and smartphones, their base station equipment, network-related electronic devices like servers and routers, and large computers.
[0003] In recent years, high-frequency electrical signals have been used in these products to transmit and process large amounts of information at high speed. However, high-frequency signals are very susceptible to attenuation, so in order to suppress transmission loss, insulating materials with excellent dielectric properties are required for use in printed circuit boards and multilayer circuit boards.
[0004] As the insulating materials mentioned above, epoxy resin compositions disclosed in Patent Documents 1 to 3 are known. Patent Document 1 discloses that an epoxy resin composition containing an epoxy resin, an active ester compound, and a triazine-containing cresol novolac resin is effective in reducing dielectric loss tangent. Patent Documents 2 and 3 disclose that resin compositions in which epoxy resin and an active ester compound are essential components can form cured products with low dielectric loss tangent and are useful as insulating materials. However, it has become clear that these epoxy resin compositions are not satisfactory for high-frequency applications.
[0005] On the other hand, Patent Document 4 reports that a resin film made from a resin composition containing a maleimide resin having a long-chain alkyl group as a non-epoxy material and a curing agent has excellent dielectric properties (low dielectric constant and low dielectric loss tangent). [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Japanese Patent Publication No. 2011-132507 [Patent Document 2] Japanese Patent Publication No. 2015-101626 [Patent Document 3] Japanese Patent Publication No. 2017-210527 [Patent Document 4] International Publication No. 2016 / 114287 [Overview of the Initiative] [Problems that the invention aims to solve]
[0007] When maleimide resin is used as an adhesive to bond a low-dielectric substrate and a copper layer due to its low dielectric properties, sufficient adhesion to copper may not be achieved. To improve adhesion to copper, it is conceivable to blend a highly polar additive into the maleimide resin, but in this case, the low dielectric properties may be impaired by the highly polar additive. Furthermore, according to the inventors' studies, even if an additive that is only highly polar is blended into the maleimide resin, the improvement in adhesion to copper is not always sufficient.
[0008] Therefore, the present disclosure aims to provide a resin composition that has excellent adhesion to copper and low dielectric properties. The present disclosure also aims to provide a cured product of the above resin composition, as well as adhesive sheets, laminates, and printed circuit boards using the above resin composition. [Means for solving the problem]
[0009] One aspect of this disclosure relates to the following resin compositions, cured products of the resin compositions, adhesive sheets, laminates and printed circuit boards. [1] A resin composition comprising (A) a maleimide resin and (B) a phosphate ester having an ethylenically unsaturated group, wherein (A) the maleimide resin is a reaction product of tetracarboxylic dianhydride (a1), an amine (a2), and maleic anhydride (a3), and the amine (a2) contains a dimer amine. [2] The resin composition according to [1] above, wherein the (B) phosphate ester having an ethylenically unsaturated group is a compound represented by the following general formula (II). [ka] [In formula (II), R 2 Z represents a hydrogen atom or a methyl group. 2 b represents a linear or branched alkylene group having 1 to 12 carbon atoms, a group in which some of the carbon atoms of the alkylene group are substituted with ether or ester bonds, or a group in which some or all of the hydrogen atoms of the alkylene group are substituted with halogen atoms, and b represents an integer from 1 to 3. If b is 2 or 3, multiple R 2 They may be the same or different from each other, and there are multiple Z 2 They may be the same or different from each other. [3] The resin composition according to [1] or [2] above, wherein the content of (B) phosphate ester having an ethylenically unsaturated group is 0.1 to 5.0 parts by mass per 100 parts by mass of the total amount of (A) maleimide resin and (B) phosphate ester having an ethylenically unsaturated group. [4](C) A resin composition according to any one of [1] to [3] above, further containing a polymerization initiator. [5] A resin composition according to any one of [1] to [4] above, for use as an adhesive for bonding a substrate and a copper layer. [6] The resin composition according to [5] above, wherein the surface roughness Ra of the adhesive surface in the copper layer is 0.1 to 0.3 μm. [7] A resin composition according to any of [1] to [4] above, for use as a copper plating primer. [8] A cured product of any of the resin compositions described in [1] to [7] above. [9] An adhesive sheet comprising a base material and an adhesive layer disposed on the base material, formed using any of the resin compositions described in [1] to [7] above.
[10] The adhesive sheet according to [9] above, wherein the thickness of the adhesive layer is 1 to 10 μm.
[11] A laminate comprising a base material, an adhesive layer disposed on the base material and formed using the resin composition according to any one of the above [1] to [7], and a copper layer disposed on the adhesive layer.
[12] The laminate according to the above
[11] , wherein the surface roughness Ra of the surface of the copper layer in contact with the adhesive layer is 0.1 to 0.3 μm.
[13] A printed wiring board formed using the laminate according to the above
[11] or
[12] . [Effects of the Invention]
[0010] According to the present disclosure, it is possible to provide a resin composition that has excellent adhesion to copper and has low dielectric properties. Further, according to the present disclosure, it is possible to provide a cured product of the above resin composition, as well as an adhesive sheet, a laminate and a printed wiring board using the above resin composition. [Modes for Carrying Out the Invention]
[0011] Hereinafter, one embodiment of the present disclosure will be specifically described, but the present disclosure is not limited thereto. In the following embodiments, it goes without saying that the constituent elements (including element steps and the like) are not necessarily essential, except for cases where they are specifically explicitly stated and cases where they are clearly considered essential in principle. This also applies to numerical values and ranges, and should not be construed as unduly limiting the present disclosure.
[0012] In the present specification, the terms "layer" and "film" encompass not only structures formed over the entire surface when observed in a plan view, but also structures formed in a partial region. The term "step" includes not only an independent step, but also a step that cannot be clearly distinguished from other steps as long as the intended purpose of the step is achieved. A numerical range indicated by "~" denotes a range that includes the numerical values stated before and after "~" as the minimum value and the maximum value, respectively. In the numerical ranges described stepwise in the present specification, the upper limit value or lower limit value of the numerical range at a certain stage can be arbitrarily combined with the upper limit value or lower limit value of the numerical range at another stage. In the numerical ranges described in the present specification, the upper limit value or lower limit value of the numerical range may be replaced with the values shown in the Examples. "A or B" only needs to include either A or B, and may include both. Unless otherwise specified, the materials exemplified in the present specification may be used singly or in combination of two or more kinds. The content of each component in the composition means the total amount of the plurality of substances present in the composition corresponding to the component, unless otherwise specified, when a plurality of substances corresponding to each component are present in the composition. In the present specification, the "solid content" refers to non-volatile components excluding volatile substances (water, solvents, etc.) contained in the resin composition, and also includes components that are liquid, syrup-like, or wax-like at room temperature (around 25°C). The term "(meth)acryloyl" means at least one of "acryloyl" and the corresponding "methacryloyl", and the same applies to other similar expressions such as (meth)acrylic acid and (meth)acrylate.
[0013] [Resin Composition] The resin composition according to the present embodiment contains (A) a maleimide resin (hereinafter also referred to as "component (A)") and (B) a phosphate ester having an ethylenically unsaturated group (hereinafter also referred to as "component (B)"). The (A) maleimide resin is a reaction product of a tetracarboxylic dianhydride (a1), an amine (a2), and maleic anhydride (a3), and the amine (a2) contains a dimer diamine.
[0014] The above resin composition exhibits excellent adhesion to copper and low dielectric properties. The reason for these effects is not clear, but it is presumed that the following occurs: When component (A) polymerizes due to heating or other means and the resin composition hardens, the ethylenically unsaturated groups of component (B) react with component (A), and component (B) is incorporated into the polymerization of component (A). As a result, the polarity of the resin composition as a whole after hardening is increased to a degree that does not impair the low dielectric properties due to the influence of the phosphate groups derived from component (B), and thus the adhesion to copper is improved.
[0015] The above resin composition can be suitably used in the manufacture of printed circuit boards (build-up boards, flexible printed wiring boards, etc.) and copper-clad laminates for printed wiring boards. Specifically, it can be used as an adhesive for bonding a substrate, such as a low-dielectric substrate, to a copper layer, and as a copper plating primer, for bonding applications between a substrate and a copper layer. Furthermore, the above resin composition is also useful as an interlayer material for semiconductors, a coating agent, a resist ink, a conductive paste, and other electrical insulating materials. In this specification, "primer" refers to a base layer that facilitates uniform adhesion of copper plating to the substrate surface when forming copper plating on the substrate, and is formed on the substrate using the above resin composition.
[0016] The following describes in more detail each component used in the resin composition of this embodiment.
[0017] <(A) Component: Maleimide resin> Component (A) according to this embodiment can be obtained by reacting a tetracarboxylic dianhydride (a1) (hereinafter also referred to as "component (a1)"), an amine (a2) (hereinafter also referred to as "component (a2)"), and maleic anhydride (a3) (hereinafter also referred to as "component (a3)"). That is, component (A) is a maleimide resin obtained by reacting components (a1), (a2), and (a3). Here, component (a2) includes a dimer amine. Component (A) may have a plurality of maleimide groups in its molecule. Component (A) may be a bismaleimide resin. Component (A) can be used alone or in combination of two or more.
[0018] (a1) As the tetracarboxylic dianhydride of component (a1), those known as raw materials for polyimides can be used. Examples of component (a1) include pyromellitic dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 1,3,3a,4,5,9b-hexahydro-5(tetrahydro-2,5-dioxo-3-furanyl)naphtho[1,2-C]furan-1,3-dione, 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-Benzophenonetetracarboxylic dianhydride, 4,4'-(4,4'-Isopropylidenediphenoxy)diphthalic acid anhydride, 1,2,3,4-Butanetetracarboxylic dianhydride, 1,2,3,4-Cyclobutanetetracarboxylic dianhydride, 1,2,3,4-Cyclopentanetetracarboxylic dianhydride, 1,2,3,4-Tetramethyl-1,2,3,4-Cyclobutanetetracarboxylic dianhydride, Bicyclo[2.2.2]octo-7-ene -2,3,5,6-tetracarboxylic dianhydride, bis(1,3-dioxo-1,3-dihydroisobenzofuran-5-carboxylic acid)1,4-phenylene, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, 4,4'-(ethyn-1,2-diyl)diphthalic anhydride, 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, dicyclohexyl-3,4,3',4'-tetracarboxylate Examples include dianhydrides of fluorocarbons, 3,4'-oxydiphthalic anhydride, 3,4'-biphthalic anhydride, norbornane-2-spiro-α-cyclopentanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic acid dianhydride, 5,5'-bis-2-norbornene-5,5',6,6'-tetracarboxylic acid-5,5',6,6'-dianhydride, and 9,9-bis[4-(3,4-dicarboxyphenoxy)phenyl]fluorene dianhydride.Among these, pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 4,4'-oxydiphthalic acid dianhydride, 4,4'-(4,4'-isopropylidene diphenoxy)diphthalic acid anhydride, 4,4'-(hexafluoroisopropylidene)diphthalic acid anhydride, and 3,3',4,4'-diphenylsulfonetetracarboxylic acid dianhydride are preferred from the viewpoint of availability, and pyromellitic dianhydride is particularly preferred from the viewpoint of heat resistance. Component (a1) can be used alone or in combination of two or more.
[0019] Component (a2) contains a dimer amine. Dimer amines are compounds derived from dimer acids, which are dimers of unsaturated fatty acids such as oleic acid, as described, for example, in Japanese Patent Publication No. 9-12712. By using a dimer amine as component (a2), the dielectric properties of the cured product can be further reduced. In this embodiment, known dimer amines can be used without particular limitation. Preferably, the dimer amine contains at least one of the compounds represented by the following general formula (1) and the compounds represented by the following general formula (2).
[0020] [ka] [ka]
[0021] In equations (1) and (2), m, n, p, and q represent integers of 1 or more selected such that m+n=6 to 17 and p+q=8 to 19, respectively. The dashed lines indicate carbon-carbon single bonds or carbon-carbon double bonds. However, if the dashed line indicates a carbon-carbon double bond, equations (1) and (2) will have a structure in which the number of hydrogen atoms bonded to each carbon atom constituting the carbon-carbon double bond is reduced by one from the number shown in equations (1) and (2).
[0022] The dimer amine may be one represented by the general formula (2) above, and in particular may be a compound represented by the following formula (3), from the viewpoint of solubility in organic solvents, heat resistance, heat adhesion, and low viscosity. [ka]
[0023] Examples of commercially available dimer amines include PRIAMINE1075 and PRIAMINE1074 (both manufactured by Croda Japan Co., Ltd.).
[0024] (a2) Component may contain other amines other than dimer amines (hereinafter also referred to as "second amines"). The second amine is an amine that does not fall under the category of dimer amines as described above. The second amine may be a diamine or a triamine, or it may be a diamine. By using an alicyclic diamine as the second amine, the dielectric constant can be made lower. By using an aromatic diamine as the second amine, the elastic modulus and Tg of the cured product can be made higher and the CTE can be made lower.
[0025] If the second amine is a diamine, examples of such diamines include 1,3-diaminopropane, norbornanediamine, 4,4-methylenedianiline, 1,3-bis[2-(4-aminophenyl)-2-propyl]benzene, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 9,9-bis(4-aminophenyl)fluorene, 9,9-bis[3-fluoro-4-aminophenyl]fluorene, 9,9-bis[4-(4-A Minophenoxy)phenyl]fluorene, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, bis(aminomethyl)norbornane, 4,4'-(hexafluoroisopropylidene)dianiline, 3(4),8(9)-bis(aminomethyl)tricyclo[5.2.1.02,6]decane, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, isophoronediamine, 4,4'-methylenebis(cyclohexylamine), 4,4'-methylenebis(2-methylcyclohexylamine 4,4'-(4-aminophenoxy)phenyl ether, 1,1-bis(4-aminophenyl)cyclohexane, 2,7-diaminofluorene, 4,4'-ethylenedianiline, 4,4'-methylenebis(2,6-diethylaniline), 4,4'-methylenebis(2-ethyl-6-methylaniline), 2,2-bis[4-(4-aminophenoxy)phenyl]propane, bis[4-(4-aminophenoxy)phenyl]methane, 4,4'-bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl Examples include [Lu]ketone, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 2,2'-dimethylbiphenyl-4,4'-diamine, (4,4'-diamino)diphenyl ether, (3,3'-diamino)diphenyl ether, paraphenylenediamine, orthophenylenediamine, metaphenylenediamine, 2,2'-dimethylbiphenyl-4,4'-diamine, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, etc. These can be used individually or in combination of two or more.
[0026] When the second amine is a triamine, examples of such triamines include tris(2-aminomethyl)amine, tris(2-aminoethyl)amine, tris(2-aminopropyl)amine, 2-(aminomethyl)-2-methyl-1,3-propanediamine, trimertriamine, 3,4,4'-triaminodiphenyl ether, 1,2,4-triaminobenzene, 1,3,5-triaminobenzene, 1,2,3-triaminobenzene, 1,3,5-triazine-2,4,6-triamine, 2,4,6-triaminopyrimidine, 1,3,5-tris(4-aminophenyl)benzene, and 1,3,5-tris(4-aminophenoxy)benzene. These can be used individually or in combination of two or more.
[0027] The second amine may contain either one of the diamines and triamines mentioned above, or both. Furthermore, the second amine may contain amines other than diamines and triamines.
[0028] (a2) The molar ratio of the second amine to the total amount of amine in component (moles of the second amine / (moles of dimer amine + moles of the second amine)) may be 70 mol% or less, 50 mol% or less, or 30 mol% or less. If this ratio is 70 mol% or less, the dielectric properties of the cured product can be made lower.
[0029] If the second amine contains a diamine, the molar ratio of the diamine in the second amine to the total amount of diamine in component (a2) (moles of diamine in the second amine / (moles of dimeramine + moles of diamine in the second amine)) may be 70 mol% or less, 50 mol% or less, or 30 mol% or less. If this ratio is 70 mol% or less, the dielectric properties of the cured product can be made lower.
[0030] Component (A) can be produced by various known methods. For example, first, components (a1) and (a2) are subjected to a polyaddition reaction at a temperature of about 60 to 120°C, preferably 70 to 90°C, for typically 0.1 to 2 hours, preferably 0.1 to 1.0 hours. Next, the resulting polyaddition is subjected to an imidation reaction, i.e., a dehydration ring-closing reaction, at a temperature of about 80 to 250°C, preferably 100 to 200°C, for about 0.5 to 30 hours, preferably 0.5 to 10 hours. Subsequently, the dehydrated ring-closing product and component (a3) are subjected to a maleimidation reaction, i.e., a dehydration ring-closing reaction, at a temperature of about 60 to 250°C, preferably 80 to 200°C, for about 0.5 to 30 hours, preferably 0.5 to 10 hours, to obtain the desired component (A).
[0031] In the imidation reaction or maleimidation reaction, various known reaction catalysts, dehydrating agents, and organic solvents can be used.
[0032] Examples of reaction catalysts include aliphatic tertiary amines such as triethylamine, aromatic tertiary amines such as dimethylaniline, heterocyclic tertiary amines such as pyridine, picoline, and isoquinoline, and organic acids such as methanesulfonic acid and p-toluenesulfonic acid monohydrate. Examples of dehydrating agents include aliphatic anhydrides such as acetic anhydride and aromatic anhydrides such as benzoic anhydride.
[0033] Organic solvents used in the above reaction include, for example, aromatic hydrocarbons such as benzene, toluene, xylene, mesitylene, and pseudocumene; alcoholic solvents such as methanol, ethanol, isopropyl alcohol, butanol, pentanol, hexanol, propanediol, and phenol; ketone solvents such as acetone, methyl isobutyl ketone, methyl ethyl ketone, pentanone, hexanone, cyclopentanone, cyclohexanone, isophorone, and acetophenone; ester solvents such as methyl cellsolve and ethyl cellsolve, methyl acetate, ethyl acetate, butyl acetate, methyl propionate, butyl formate, and γ-butyrolactone; and ethylene glycol mono-n-butyl ester. Examples include glycol ether solvents such as ethyl glycol mono-iso-butyl ether, ethylene glycol mono-tert-butyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol mono-iso-butyl ether, triethylene glycol monoethyl ether, triethylene glycol mono-n-butyl ether, and tetraethylene glycol mono-n-butyl ether; and nitrogen-containing compounds such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 3-methoxy-N,N-dimethylpropanamide, and 3-butoxy-N,N-dimethylpropanamide. Organic solvents can be used individually or in combination of two or more. From the viewpoint of solubility, it is preferable to use toluene, xylene, mesitylene, or pseudocumene in combination with methanol or ethanol.
[0034] Component (A) can be purified by various known methods, and its purity can be increased. For example, first, component (A) dissolved in an organic solvent and pure water are placed in a separatory funnel. Next, the separatory funnel is shaken and allowed to stand. After the aqueous layer and organic layer separate, component (A) can be purified by recovering only the organic layer.
[0035] An example of the expected structure of component (A) produced by the above method is shown in the general formula (4) below. [ka]
[0036] In general formula (4), each X independently represents a tetravalent organic group, each Y independently represents a divalent organic group, and a represents an integer of 1 or more. However, at least one of the multiple Ys represents a divalent organic group derived from the dimer amine described above. Furthermore, X and Y may be organic groups having an aliphatic group, an alicyclic structure, or an aromatic ring, and they may contain heteroatoms.
[0037] The molecular weight of component (A) can be controlled by the number of moles of component (a1) and component (a2), and the smaller the number of moles of component (a1) is compared to the number of moles of component (a2), the smaller the molecular weight can be. For the purpose of making it easier to achieve the effects of this disclosure, the number of moles of component (a1) per mole of component (a2), i.e., [number of moles of component (a1)] / [number of moles of component (a2)] is usually in the range of 0.30 to 0.95, preferably 0.50 to 0.85.
[0038] (A) The molecular weight of component (A) is preferably 3,000 to 40,000 in weight-average molecular weight (Mw), more preferably 4,000 to 30,000, and even more preferably 5,000 to 28,000, or 7,000 to 27,000, from the viewpoint of solubility in solvents and heat resistance. When the weight-average molecular weight is 40,000 or less, solubility in organic solvents is good, and when it is 3,000 or more, a sufficient effect of improving heat resistance tends to be obtained. Mw can be measured by gel permeation chromatography (GPC) and converted using a calibration curve for standard polystyrene.
[0039] As the maleimide resin, the maleimide resin represented by the above general formula (4) is preferred from the viewpoint of superior adhesion and dielectric properties.
[0040] (A) As component, commercially available compounds can be used. Specifically, for example, SFR-2300MR-T (synthesized from an amine containing dimer amine, tetracarboxylic dianhydride, and maleic anhydride) manufactured by Resonaq Corporation, BMI-3000 Commercial Grade (synthesized from dimer amine, pyromellitic dianhydride, and maleic anhydride), BMI-1500, BMI-1700, and BMI-5000 manufactured by DESIGNER MOLECULES Inc. can be suitably used.
[0041] The content of component (A) may be 95 to 99.9 parts by mass, preferably 98 to 99.8 parts by mass, based on 100 parts by mass of the total amount of components (A) and (B).
[0042] <(B) Component: Phosphate ester having an ethylenically unsaturated group> (B) Phosphate esters having an ethylenically unsaturated group are compounds having an ethylenically unsaturated group and a phosphate group. "Ethylenelycol" refers to an organic group having an ethylenically unsaturated bond (carbon-carbon double bond). "Phosphate group" refers to a group obtained by removing 1 to 3 hydrogen atoms from phosphoric acid (H3PO4). Component (B) can be used individually or in combination of two or more.
[0043] The number of ethylenically unsaturated groups in component (B) is, for example, 1 to 3, preferably 1 or 2. Component (B) preferably has at least one group selected from vinyl group, vinylene group, vinylidene group, (meth)acryloyl group and (meth)acryloyloxy group as the ethylenically unsaturated group, and more preferably has a (meth)acryloyloxy group.
[0044] The number of phosphate groups in component (B) is, for example, 1 to 2, and preferably 1.
[0045] Component (B) is preferably a compound represented by the following general formula (I).
[0046]
Chemical Formula
[0047] The compound represented by general formula (I) is preferably a compound represented by the following general formula (II) from the viewpoint of having more excellent adhesion to copper and being capable of maintaining low dielectric properties.
[0048]
Chemical Formula
[0049] Specific examples of compounds represented by general formula (II) include 2-methachlorooxyethyl acid phosphate (also known as 2-methachloroyloxyethyl acid phosphate), bis(2-methachlorooxyethyl) acid phosphate (also known as bis(2-methachloroyloxyethyl) acid phosphate), 6-methachlorooxyhexyl acid phosphate, 10-methachlorooxydecyl acid phosphate, 12-methachlorooxidedecyl acid phosphate, 11-methachlorooxy-3,6,9-trioxaundecyl acid phosphate, 10-methachlorooxycaprolactone acid phosphate, and 6-methachlorooxy-2,2,3,3,4,4,5,5-octafluorohexyl acid phosphate. These can be used individually or in combination of two or more. From the viewpoint of having better adhesion to copper while maintaining low dielectric properties, bis(2-methachlorooxyethyl) acid phosphate may be used.
[0050] From the viewpoint of having better adhesion to copper and maintaining low dielectric properties, the content of component (B) may be 0.1 parts by mass or more, 0.2 parts by mass or more, 0.3 parts by mass or more, 0.4 parts by mass or more, or 0.5 parts by mass or more, per 100 parts by mass of the total amount of components (A) and (B). The content of component (B) may be 5.0 parts by mass or less or 3.0 parts by mass or less, per 100 parts by mass of the total amount of components (A) and (B), and from the viewpoint of having better adhesion to copper and maintaining low dielectric properties, it may be 2.5 parts by mass or less, 2.2 parts by mass or less, or 2.0 parts by mass or less. When the content of component (B) is 2.5 parts by mass or less, the proportion of unreacted component (B) in the polymerization of component (A) and component (B) is reduced, and the decrease in adhesion to copper due to unreacted component (B) tends to be suppressed. From these perspectives, the content of component (B) may be 0.1 to 5.0 parts by mass, 0.1 to 3.0 parts by mass, 0.1 to 2.5 parts by mass, 0.2 to 2.5 parts by mass, 0.3 to 2.5 parts by mass, 0.4 to 2.2 parts by mass, or 0.5 to 2.0 parts by mass, based on 100 parts by mass of the total amount of components (A) and (B).
[0051] <(C) Component: Polymerization initiator> The resin composition of this embodiment may further contain a polymerization initiator (C) (hereinafter also referred to as "component (C)"). The resin composition of this embodiment tends to have better adhesion to copper and maintain low dielectric properties when it further contains component (C). Examples of component (C) include organic peroxides, imidazole compounds, phosphine compounds, phosphonium salt compounds, etc. These can be used individually or in combination of two or more. The polymerization initiator (C) may be at least one selected from the group consisting of organic peroxides, imidazole compounds, phosphine compounds, and phosphonium salt compounds.
[0052] Examples of organic peroxides include methyl ethyl ketone peroxide, methylcyclohexanone peroxide, methyl acetate peroxide, acetylacetone peroxide, 1,1-bis(t-butyl peroxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-hexyl peroxy)cyclohexane, 1,1-bis(t-hexyl peroxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-butyl peroxy)cyclohexane, and 2,2-bis(4,4-di-t-butyl (Turperoxycyclohexyl)propane, 1,1-bis(t-butylperoxy)cyclododecane, n-butyl 4,4-bis(t-butylperoxy)valerate, 2,2-bis(t-butylperoxy)butane, 1,1-bis(t-butylperoxy)-2-methylcyclohexane, t-butyl hydroperoxide, p-menthane hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, t-hexyl hydroperoxide, dicumyl peroxide, 2,5-dimethyl-2 ,5-bis(t-butylperoxy)hexane, α,α'-bis(t-butylperoxy)diisopropylbenzene, t-butylcumyl peroxide, di-t-butyl peroxide, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexine-3, isobutyryl peroxide, 3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, lauroyl peroxide, cinnamate peroxide, m-toluyl peroxide, benzoyl peroxide, diisopropyl peroxide -Oxydicarbonate, bis(4-t-butylcyclohexyl)peroxydicarbonate, di-3-methoxybutyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, di-sec-butyl peroxydicarbonate, di(3-methyl-3-methoxybutyl)peroxydicarbonate, di(4-t-butylcyclohexyl)peroxydicarbonate, α,α'-bis(neodecanoylperoxy)diisopropylbenzene, cumylperoxyneodecanoate, 1,1,3,3,-Tetramethylbutyl peroxyneodecanoate, 1-cyclohexyl-1-methylethyl peroxyneodecanoate, t-hexyl peroxyneodecanoate, t-butyl peroxyneodecanoate, t-hexyl peroxypivalate, t-butyl peroxypivalate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, 1-cyclohexyl-1-methylethyl peroxy-2-ethylhexanoate, t-hexyl peroxy-2-ethylhexanoate, t-butyl peroxy-2-ethylhexanoate, t-butyl peroxyisobutyrate, t-butyl Examples include peroxymalic acid, t-butyl peroxylaurate, t-butyl peroxy-3,5,5-trimethylhexanoate, t-butyl peroxyisopropyl monocarbonate, t-butyl peroxy-2-ethylhexyl monocarbonate, 2,5-dimethyl-2,5-bis(benzoylperoxy)hexane, t-butyl peroxyacetate, t-hexyl peroxybenzoate, t-butyl peroxy-m-toluylbenzoate, t-butyl peroxybenzoate, bis(t-butylperoxy)isophthalate, t-butyl peroxyallyl monocarbonate, and 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone. These can be used individually or in combination of two or more. Among these organic peroxides, dicumyl peroxide, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, and α,α'-bis(t-butylperoxy)diisopropylbenzene are preferred, with dicumyl peroxide being more preferred.
[0053] Examples of imidazole compounds include 2-ethyl-4-methylimidazole, 2-methylimidazole, 2-ethylimidazole, 2,4-dimethylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 1-vinyl-2-methylimidazole, 1-propyl-2-methylimidazole, 2-isopropylimidazole, 1-cyanomethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, and 1-cyanoethyl-2-phenylimidazole. These can be used individually or in combination of two or more.
[0054] Examples of phosphine compounds include primary phosphines, secondary phosphines, and tertiary phosphines. Specific examples of primary phosphines include alkyl phosphines such as ethylphosphine and propylphosphine, and phenylphosphine. Specific examples of secondary phosphines include dialkyl phosphines such as dimethylphosphine and diethylphosphine, and secondary phosphines such as diphenylphosphine, methylphenylphosphine, and ethylphenylphosphine. Tertiary phosphines include trialkyl phosphines such as trimethylphosphine, triethylphosphine, tributylphosphine, and trioctylphosphine, tricyclohexylphosphine, triphenylphosphine, alkyldiphenylphosphine, dialkylphenylphosphine, tripenzylphosphine, tritrillphosphine, tri-p-styrylphosphine, tris(2,6-dimethoxyphenyl)phosphine, tri-4-methylphenylphosphine, tri-4-methoxyphenylphosphine, and tri-2-cyanoethylphosphine. These can be used individually or in combination of two or more.
[0055] Examples of phosphonium salt compounds include compounds having tetraphenylphosphonium salts, alkyltriphenylphosphonium salts, and tetraalkylphosphonium. Specifically, these include tetraphenylphosphonium-thiocyanate, tetraphenylphosphonium-tetra-p-methylphenylborate, butyltriphenylphosphonium-thiocyanate, tetraphenylphosphonium-phthalic acid, tetrabutylphosphonium-1,2-cyclohexyldicarboxylic acid, tetrabutylphosphonium-1,2-cyclohexyldicarboxylic acid, and tetrabutylphosphonium-lauric acid. These can be used individually or in combination of two or more.
[0056] The content of component (C) is not particularly limited, but is preferably 0.1 to 10.0 parts by mass, and more preferably 0.5 to 5.0 parts by mass, per 100 parts by mass of component (A).
[0057] <(D) Component: Organic solvent> The resin composition of this embodiment may further contain an organic solvent (D) (hereinafter also referred to as "component (D)"). Component (D) is not particularly limited as long as it dissolves components (A), (B), and (C). (D) Component can include, for example, aromatic hydrocarbons such as benzene, toluene, xylene, mesitylene, and pseudocumene; alcoholic solvents such as methanol, ethanol, isopropyl alcohol, butanol, pentanol, hexanol, propanediol, and phenol; ketone solvents such as acetone, methyl isobutyl ketone, methyl ethyl ketone, pentanone, hexanone, cyclopentanone, cyclohexanone, isophorone, and acetophenone; ester solvents such as methyl cellsolve and ethyl cellsolve, methyl acetate, ethyl acetate, butyl acetate, methyl propionate, and butyl formate; and glycol ether solvents such as ethylene glycol mono-n-butyl ether, ethylene glycol mono-iso-butyl ether, ethylene glycol mono-tert-butyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol mono-iso-butyl ether, triethylene glycol mono-n-butyl ether, and tetraethylene glycol mono-n-butyl ether. One or more of these can be used in combination.
[0058] The content of component (D) is not particularly limited and may be such that the total solid content in the resin composition of this embodiment is 30 to 70% by mass, or it may be such that it is 35 to 65% by mass or 40 to 60% by mass.
[0059] The resin composition of this embodiment is prepared according to generally accepted methods. Examples of preparation methods include melt mixing, powder mixing, and solution mixing. In addition, other materials besides components (A), (B), (C), and (D), such as inorganic fillers, mold release agents, flame retardants, ion trapping agents, antioxidants, adhesion promoters, stress reducers, colorants, and coupling agents, may be added insofar as they do not impair the effects of the present disclosure. Furthermore, the resin composition of this embodiment may also contain resins other than component (A), such as epoxy resins, acrylate compounds, vinyl compounds, benzoxazine compounds, and bismaleimide compounds.
[0060] Inorganic fillers are added to resin compositions to reduce their thermal expansion coefficient and improve their moisture resistance. As inorganic fillers, any known materials can be used, such as fused silica, crystalline silica, cristobalite, alumina, silicon nitride, aluminum nitride, boron nitride, titanium oxide, glass fibers, and magnesium oxide. The average particle size and shape of these inorganic fillers can be selected according to the application. Spherical alumina, spherical fused silica, and glass fibers are particularly preferred. These can be used individually or in combination of two or more.
[0061] Release agents are added to improve mold release properties. Known release agents can be used, such as carnauba wax, rice wax, candelilla wax, polyethylene, polyethylene oxide, polypropylene, montanic acid, montan wax (an ester compound of montanic acid with saturated alcohol, 2-(2-hydroxyethylamino)ethanol, ethylene glycol, glycerin, etc.), stearic acid, stearic acid esters, and stearic acid amides. These can be used individually or in combination of two or more.
[0062] Flame retardants are added to impart flame retardancy. Known flame retardants can be used and are not particularly limited. Examples of flame retardants include phosphazene compounds, silicone compounds, zinc molybdate-supported talc, zinc molybdate-supported zinc oxide, aluminum hydroxide, magnesium hydroxide, and molybdenum oxide. These can be used individually or in combination of two or more.
[0063] Ion trapping agents are added to liquid resin compositions to capture ionic impurities and prevent thermal and hygroscopic degradation. Any known ion trapping agent can be used, and there are no particular limitations. Examples of ion trapping agents include hydrotalcites, bismuth hydroxide compounds, and rare earth oxides. These can be used individually or in combination of two or more.
[0064] Furthermore, the resin composition of this embodiment may further contain, as other components not corresponding to components (A), (B), (C), and (D), phosphate esters without ethylenically unsaturated groups or ethylenically unsaturated compounds without phosphate groups. However, from the viewpoint of having better adhesion to copper and maintaining low dielectric properties, the resin composition does not need to contain phosphate esters without ethylenically unsaturated groups or ethylenically unsaturated compounds without phosphate groups. The content of these compounds may be 10% by mass or less, 5% by mass or less, 3% by mass or less, 1% by mass or less, or 0% by mass, based on the total solid content of the resin composition.
[0065] [Cured product] The cured product of this embodiment can be obtained by curing the resin composition of this embodiment. Specifically, it can be obtained by heat-treating the resin composition at approximately 150 to 250°C for approximately 5 minutes to 3 hours.
[0066] The shape and thickness of the cured product in this embodiment can be adjusted as appropriate depending on the application and are not particularly limited, but when used for bonding a substrate and a copper layer, it can be in the form of a sheet with a thickness of 0.5 to 10 μm. The thickness of the cured product may be 1 to 10 μm, or it may be 1 to 5 μm or 1 to 3 μm.
[0067] [Adhesive Sheet] The adhesive sheet of this embodiment comprises a substrate and an adhesive layer formed on the substrate using the resin composition of the above embodiment. The adhesive sheet of this embodiment can be obtained, for example, by applying the resin composition of this embodiment to a substrate (sheet substrate) and drying it. Examples of the substrate include organic substrates such as polyimide, polyimide-silica hybrid, polyamide, polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polymethyl methacrylate resin (PMMA), polystyrene resin (PSt), polycarbonate resin (PC), acrylonitrile-butadiene-styrene resin (ABS), ethylene terephthalate, phenol, phthalic acid, hydroxynaphthoic acid, and p-hydroxybenzoic acid (so-called liquid crystal polymers; such as "Vecter" manufactured by Kuraray Co., Ltd.). Among these, polyimide film, particularly polyimide-silica hybrid film, is preferred in terms of heat resistance and dimensional stability. Furthermore, the above-mentioned substrate may be a metal such as glass, iron, aluminum, 42 alloy, or copper, or an inorganic substrate such as ITO, silicon, or silicon carbide.
[0068] The thickness of the adhesive layer varies depending on the application, but when used for bonding a substrate to a copper layer, the thickness of the adhesive layer can be 0.5 to 10 μm. The solid content of each component in the adhesive layer other than volatile substances (components (A) to (C) and other components) is the same as the solid content of each component in the resin composition forming the adhesive layer. The thickness of the adhesive layer may be 1 to 10 μm, or it may be 1 to 5 μm or 1 to 3 μm.
[0069] <Laminate> The laminate of this embodiment comprises a base material, an adhesive layer formed using the resin composition of the above embodiment and disposed on the base material, and a copper layer disposed on the adhesive layer. The laminate may be obtained using the adhesive sheet of the above embodiment. That is, the laminate may be formed by forming a copper layer on the adhesive layer of the adhesive sheet of the above embodiment. The thickness of the adhesive layer of the laminate may be 0.5 to 10 μm. Furthermore, the laminate may be cured by heating or other means.
[0070] Methods for forming a copper layer on an adhesive layer include laminating a copper layer, such as copper foil, onto the adhesive layer by vacuum lamination, heat pressing, or roll lamination; forming a copper layer by depositing copper onto the adhesive layer by vacuum deposition or sputtering; and forming a copper layer by plating copper onto the adhesive layer by electrolytic plating or electroless plating. When forming a copper layer by plating copper onto an adhesive layer, the adhesive layer may be a copper plating primer layer. Furthermore, when forming a copper layer on an adhesive layer by electrolytic plating, a seed copper layer may be formed on the adhesive layer beforehand by deposition or the like, and then electrolytic plating may be performed on top of it.
[0071] The surface roughness Ra of the copper layer in contact with the adhesive layer can be, for example, 0.1 to 0.3 μm. Note that the surface roughness Ra here refers to the arithmetic mean roughness (Ra) as defined in JIS B 0601-2001.
[0072] The laminate of this embodiment can be cured by heat treatment to harden the adhesive layer. The heat treatment conditions may be, for example, a heating temperature of 150 to 250°C and a heating time of 5 minutes to 3 hours.
[0073] <Printed wiring board> The printed circuit board of this embodiment uses the laminate of the above embodiment. The printed circuit board of this embodiment can be obtained, for example, by soft etching the copper layer surface of the laminate of the above embodiment to form a circuit, and then bonding the adhesive layer surface of the adhesive sheet of the above embodiment onto it and heating and pressing. [Examples]
[0074] The present disclosure will be described in detail below with reference to examples and comparative examples, but this disclosure is not limited to these. In each example, "parts" and "%" are based on mass unless otherwise specified.
[0075] [Methods for evaluating physical properties] <Copper adhesion> The resin compositions obtained in the examples and comparative examples described later were applied using an applicator to the smooth surface of copper foil (manufactured by Mitsui Mining & Smelting Co., Ltd., product name "3EC-M2S-VLP", thickness: 12 μm, surface roughness Ra: 0.28 μm of the smooth surface) to a thickness of 1 μm after drying. A laminated film (1) was prepared by drying it in an oven at 110°C for 10 minutes, forming an adhesive layer on the smooth surface of the copper foil. Subsequently, the adhesive layer surface of the laminated film (1) and the smooth surface of the newly prepared copper foil were laminated facing each other, and the two were pressed together using a vacuum laminator under conditions of a pressure of 0.5 MPa, a heating temperature of 80°C, and a pressurizing time of 120 seconds to obtain a laminate (1) in which copper foil, adhesive layer, and copper foil were laminated in this order. The laminate (1) was heated in a hot air drying oven at 200°C for 1 hour to cure it. After curing, one copper foil of the laminate (1) was fixed to the lower base with a clamp. The other copper foil of the laminate (1) was attached to the upper movable arm, and the copper foil was pulled upward to peel it off the laminate (1), thereby measuring the 180° peel strength (unit: kN / m). The 180° peel strength was measured at room temperature with a tensile speed of 5 mm / s using a benchtop precision universal testing machine (manufactured by Shimadzu Corporation, product name "Autograph AGX-S"). Furthermore, when the peeling position (peeling mode) was observed during peeling, it was found that both the example and comparative example exhibited interfacial peeling. Interfacial peeling means that the copper foil attached to the movable arm peeled off at the interface with the adhesive layer of the laminate (1).
[0076] <Relative permittivity and dielectric loss tangent> The resin compositions obtained in the examples and comparative examples described later were applied to a film vin (registered trademark) (PET film, manufactured by ZACROS Corporation, product name "NS14", silicone-free, thickness 75 μm) using an applicator to a dry thickness of 100 μm. A hot air drying oven was used to dry the film at 110°C for 10 minutes to produce a resin film with an adhesive layer formed on the film vin. The adhesive layer surface of the obtained resin film was laminated with the smooth surface of copper foil (manufactured by Mitsui Mining & Smelting Co., Ltd., product name "3EC-M2S-VLP", thickness: 12 μm, surface roughness Ra: 0.28 μm) facing each other. The films were then pressed together using a vacuum laminator under conditions of a pressure of 0.5 MPa, a heating temperature of 80°C, and a pressurizing time of 120 seconds. The film vin was then peeled off to obtain a laminated film (2) with an adhesive layer formed on the smooth surface of the copper foil. Next, the adhesive layer surface of the laminated film (2) and the smooth surface of the newly prepared copper foil were laminated together so that they faced each other, and the laminates were pressed together by vacuum lamination under the same conditions as above to obtain a laminate (2) in which copper foil, adhesive layer, and copper foil were laminated in this order. The laminate (2) was heated in a hot air drying oven at 180°C for 1 hour to cure it. After curing, the copper foil on both sides of the laminate (2) was removed by etching, and it was dried at 80°C for 1 hour to prepare a 5cm x 6cm test piece. The relative permittivity (Dk) and dielectric loss tangent (Df) of the test piece were measured at 10GHz using a vector network analyzer 8364B (product name, manufactured by Agilent Technologies). If the relative permittivity is 2.8 or less and the dielectric loss tangent is 0.0035 or less, it can be said that the dielectric properties are sufficiently low.
[0077] [Synthesis of maleimide resin] In a 2L pressure-resistant SUS container (manufactured by Todoroki Sangyo Co., Ltd.) equipped with a condenser, separation tank, nitrogen inlet tube, thermocouple, and stirrer, and capable of carrying out the reaction under pressure while refluxing the solvent, 111 parts by mass of pyromellitic dianhydride (manufactured by Daicel Corporation), 907 parts by mass of toluene (manufactured by Wako Pure Chemical Industries, Ltd.), and 200 parts by mass of methanol (manufactured by Daishin Chemical Co., Ltd.) were added. Next, nitrogen gas was introduced into the container to pressurize it to a gauge pressure of 250 kPa, and the temperature was raised to 80°C and maintained for 0.5 hours. Subsequently, 368 parts by mass of dimeramine (trade name "PRIAMINE 1075", manufactured by Croda Japan Co., Ltd.) were added dropwise at a dropping rate of 12.3 g / min. After addition, the temperature was maintained at 80°C for 0.5 hours, and then 6.5 parts by mass of methanesulfonic acid was added. After that, the temperature was raised to 160°C while removing the alcohol-based solvent from the reaction solution. After raising the temperature, a dehydration and ring-closing reaction was carried out at 160°C for 2 hours to remove water and alcohol-based solvents from the reaction solution, obtaining a solution containing the intermediate polyimide resin. Subsequently, the solution containing the obtained polyimide resin was cooled to 130°C, and 50 parts by mass of maleic anhydride (manufactured by Fuso Chemical Industry Co., Ltd.) was added. Then, the temperature was raised to 160°C. After raising the temperature, a dehydration and ring-closing reaction was carried out at 160°C for 4 hours to remove water from the reaction solution, obtaining a solution containing maleimide resin.
[0078] The solution containing the obtained maleimide resin was placed in a separatory funnel, 1200 parts by mass of pure water were added, the separatory funnel was shaken, and the mixture was allowed to stand. After standing, the organic layer and the aqueous layer were separated, and only the organic layer was recovered. The recovered organic layer was placed in a 1 L glass container equipped with a condenser, nitrogen inlet tube, thermocouple, stirrer, and vacuum pump, heated to 88-93°C to remove water, then heated to 115°C, and the solvent was partially removed for 0.5 hours under a reduced pressure of 0.1 MPa from atmospheric pressure to obtain a maleimide resin (A-1) solution. The weight-average molecular weight (Mw) of maleimide resin (A-1) was 17200, and the solid content of the maleimide resin (A-1) solution was 58.9% by mass. The weight-average molecular weight (Mw) of the maleimide resin and the solid content of the maleimide resin (A-1) solution were determined by the following method.
[0079] <Weight average molecular weight (Mw)> The weight-average molecular weight (Mw) of maleimide resin (A-1) was measured by GPC (gel permeation chromatography). A sample of maleimide resin (A-1) dissolved in tetrahydrofuran (THF) to a concentration of 3% by mass was injected in 50 μL into a column heated to 30°C (one GL-R420 column and one GL-R440 column, both manufactured by Hitachi High-Tech Fielding Co., Ltd.). Measurement was performed using THF as the developing solvent at a flow rate of 1.6 mL / min. An L-3350 RI detector (manufactured by Hitachi, Ltd.) was used, and the weight-average molecular weight (Mw) was calculated from the elution time using a molecular weight / elution time curve prepared using standard polystyrene (manufactured by Tosoh Corporation).
[0080] <Solid content> The solid content of the maleimide resin (A-1) solution was calculated using the following formula: X1g of maleimide resin (A-1) solution was placed in an aluminum petri dish weighing Z1g, and after heating at 150°C for 0.5 hours, the weight of the aluminum petri dish (including the remaining resin composition) was Z2g. Solid content (unit: mass %) = {(Z2-Z1) / X1} × 100
[0081] [Example 1] In a 500 ml four-necked flask equipped with a stirrer, 99.7 parts by mass (solid content equivalent) of the maleimide resin (A-1) obtained in Synthesis Example 1, 0.3 parts by mass of ethylenically unsaturated phosphate ester (trade name "P-1M", manufactured by Kyoeisha Chemical Co., Ltd.), and 100 parts by mass of toluene were charged and stirred at 60°C for 0.5 hours. To the resulting solution, 1.0 part by mass of a polymerization initiator (manufactured by NOF Corporation, trade name "Parkmill D") was added and stirred at 60°C for 3 hours to obtain a resin composition. The amounts of each component and the results of the physical property evaluation are shown in Table 1. In Table 1, the amounts of components (A) to (D) are shown in parts by mass.
[0082] [Examples 2-4, Comparative Examples 1-3] Resin compositions for Examples 2-4 and Comparative Examples 1-3 were obtained in the same manner as in Example 1, except that the type and amount of one or more components from maleimide resin, phosphate ester having an ethylenically unsaturated group, phosphate ester without an ethylenically unsaturated group, ethylenically unsaturated compound without a phosphate group, and polymerization initiator were changed as shown in Table 1. The amount of each component and the results of the physical property evaluation are shown in Table 1. In Table 1, the amounts of components (A) to (D) are in parts by mass. The details of components (A) to (D) are as follows.
[0083] (A) Component: Maleimide resin (A-1) Maleimide resin from synthesis example 1 (weight-average molecular weight 16000)
[0084] (B) Component: Phosphate ester having an ethylenically unsaturated group (B-1)P-1M (Trade name, 2-Methachlorooxyethyl acid phosphate, manufactured by Kyoeisha Chemical Co., Ltd.) (B-2)P-2M (Product name: Bis(2-methchloroyloxyethyl) acid phosphate, manufactured by Kyoeisha Chemical Co., Ltd.)
[0085] (B') Component: Phosphate ester without ethylenically unsaturated groups (B'-1)JP506H (Product name, butoxyethyl acid phosphate, manufactured by Johoku Chemical Industry Co., Ltd.)
[0086] (B) Component: Ethylene unsaturated compound that does not contain a phosphate group (B"-1) MIRAMER M1084 (product name, isooctyl acrylate, manufactured by Miwon Specialty Chemical)
[0087] (C) Ingredient: Polymerization initiator (C-1) Perkmyl D (product name, dicumyl peroxide, manufactured by NOF Corporation)
[0088] (D) Component: Organic solvent (D-1) Toluene
[0089] Table 1
Claims
1. (A) Maleimide resin and (B) Phosphate ester having an ethylenically unsaturated group, The (A) maleimide resin is a reaction product of tetracarboxylic dianhydride (a1), amine (a2), and maleic anhydride (a3). A resin composition wherein the amine (a2) contains a dimer amine.
2. The resin composition according to claim 1, wherein the (B) phosphate ester having an ethylenically unsaturated group is a compound represented by the following general formula (II). 【Chemistry 1】 [In formula (II), R 2 Z represents a hydrogen atom or a methyl group. 2 b represents a linear or branched alkylene group having 1 to 12 carbon atoms, a group in which some of the carbon atoms of the alkylene group are substituted with ether or ester bonds, or a group in which some or all of the hydrogen atoms of the alkylene group are substituted with halogen atoms, and b represents an integer from 1 to 3. When b is 2 or 3, multiple R 2 These may be the same or different from each other, and there may be multiple Z 2 They may be the same or different from each other.
3. The resin composition according to claim 1, wherein the content of (B) phosphate ester having an ethylenically unsaturated group is 0.1 to 5.0 parts by mass with respect to 100 parts by mass of the total amount of (A) maleimide resin and (B) phosphate ester having an ethylenically unsaturated group.
4. (C) The resin composition according to claim 1, further comprising a polymerization initiator.
5. The resin composition according to claim 1, for use as an adhesive for bonding a substrate and a copper layer.
6. The resin composition according to claim 5, wherein the surface roughness Ra of the adhesive surface in the copper layer is 0.1 to 0.3 μm.
7. The resin composition according to claim 1, for use as a copper plating primer.
8. A cured product of the resin composition according to any one of claims 1 to 7.
9. An adhesive sheet comprising a base material and an adhesive layer disposed on the base material, formed using the resin composition described in any one of claims 1 to 7.
10. The adhesive sheet according to claim 9, wherein the thickness of the adhesive layer is 1 to 10 μm.
11. A laminate comprising a base material, an adhesive layer disposed on the base material and formed using a resin composition according to any one of claims 1 to 7, and a copper layer disposed on the adhesive layer.
12. The laminate according to claim 11, wherein the surface roughness Ra of the surface of the copper layer in contact with the adhesive layer is 0.1 to 0.3 μm.
13. A printed circuit board comprising the laminate described in claim 11.
Citation Information
Patent Citations
Epoxy resin composition
JP2011132507A
Resin composition
JP2015101626A
Resin composition
JP2017210527A
Resin film for flexible printed circuit board, metal foil provided with resin, coverlay film, bonding sheet, and flexible printed circuit board
WO2016114287A1